Type I and Type II Interferon Antagonism Strategies Used by Paramyxoviridae: Previous and New Discoveries, in Comparison - Giuseppe Pisanelli; Ugo Pagnini; Giuseppe Iovane; Adolfo García-Sastre (Viruses, 2022)
Paramyxoviridae is a viral family within the order of Mononegavirales; they are negative single-strand RNA viruses that can cause significant diseases in both humans and animals. In order to replicate, paramyxoviruses–as any other viruses–have to bypass an important protective mechanism developed by the host’s cells: the defensive line driven by interferon. Once the viruses are recognized, the cells start the production of type I and type III interferons, which leads to the activation of hundreds of genes, many of which encode proteins with the specific function to reduce viral replication. Type II interferon is produced by active immune cells through a different signaling pathway, and activates a diverse range of genes with the same objective to block viral replication. As a result of this selective pressure, viruses have evolved different strategies to avoid the defensive function of interferons. The strategies employed by the different viral species to fight the interferon system include a number of sophisticated mechanisms. Here we analyzed the current status of the various strategies used by paramyxoviruses to subvert type I, II, and III interferon responses.